QoS-Aware Resource Management Approaches in Webservers. (Computer (00189162), 2008)
The article discusses quality-of-service (QoS)-aware resource management approaches in webservers. They include the application of queuing models to infer expected delays of a traffic class in webservers based on the input load change. Studies were also conducted to evaluate the use of feedback control approaches to regulate the processing-rate allocation in response to measured deviations from the desired performance. A feedback control design for QoS differentiation was presented by C. Lu and his colleagues.